Fragile regions and not functional constraints predominate in shaping gene organization in the genus Drosophila - von Grotthuss, Marcin; Ashburner, Michael; Ranz, José M. (Genome Research, 2010)
During evolution, gene repatterning across eukaryotic genomes is not uniform. Some genomic regions exhibit a gene organization conserved phylogenetically, while others are recurrently involved in chromosomal rearrangement, resulting in breakpoint reuse. Both gene order conservation and breakpoint reuse can result from the existence of functional constraints on where chromosomal breakpoints occur or from the existence of regions that are susceptible to breakage. The balance between these two mechanisms is still poorly understood. Drosophila species have very dynamic genomes and, therefore, can be very informative. We compared the gene organization of the main five chromosomal elements (Muller's elements A–E) of nine Drosophila species. Under a parsimonious evolutionary scenario, we estimate that 6116 breakpoints differentiate the gene orders of the species and that breakpoint reuse is associated with ∼80% of the orthologous landmarks. The comparison of the observed patterns of change in gene organization with those predicted under different simulated modes of evolution shows that fragile regions alone can explain the observed key patterns of Muller's element A (X chromosome) more often than for any other Muller's element. High levels of fragility plus constraints operating on ∼15% of the genome are sufficient to explain the observed patterns of change and conservation across species. The orthologous landmarks more likely to be under constraint exhibit both a remarkable internal functional heterogeneity and a lack of common functional themes with the exception of the presence of highly conserved noncoding elements. Fragile regions rather than functional constraints have been the main determinant of the evolution of the Drosophila chromosomes.
10.1101/gr.103713.109